Lessons learned from 25 years of process improvement: the rise and fall of the NASA software engineering laboratory - Basili, Victor R.; McGarry, Frank E.; Pajerski, Rose; Zelkowitz, Marvin V. (Proceedings - International Conference on Software Engineering, 2002)
For 25 years the NASA/GSFC Software Engineering Laboratory (SEL) has been a major resource in software process improvement activities. But due to a changing climate at NASA, agency reorganization, and budget cuts, the SEL has lost much of its impact. In this paper we describe the history of the SEL and give some lessons learned on what we did right, what we did wrong, and what others can learn from our experiences. We briefly describe the research that was conducted by the SEL, describe how we evolved our understanding of software process improvement, and provide a set of lessons learned and hypotheses that should enable future groups to learn from and improve on our quarter century of experiences.